Profilul familiei românești contemporane - Popescu, Raluca (Calitatea Vieții, 2010)
This study tries to configure the profile of the contemporary Romanian family. The first part of the paper presents a comparative analysis at the European level on macro-level indicators from Eurostat, with the aim of showing the main trends in nuptial and reproductive behaviour in Romania. Analysis on survey data is presented in the second part, in order to explore the family life styles and the dominant perceptions regarding family and couple life. The quality of family life, the most important conditions for a happy marriage, the divorces reasons, the satisfaction with family life, the problems which couples have to deal with, the sexual behaviours and attitudes towards sexuality are the main issues debated. The data bases used are: “Diagnosis of Quality of Life” 1990–1999, 2003, 2006 (RIQL), Public Opinion Barometer “Life couple” 2007 (Soros Foundation) and “Family Life” 2008 (Soros Foundation).